2019
DOI: 10.1016/j.molmed.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Breast Cancer: Pathways to Understand Risk and Prevention

Abstract: Several studies have made strong efforts to understand how age and parity modulate the risk of breast cancer. A holistic understanding of the dynamic regulation of the morphological, cellular, and molecular milieu of the mammary gland offers insights into the drivers of breast cancer development as well as into potential prophylactic interventions, the latter being a longstanding ambition of the research and clinical community aspiring to eradicate the disease. In this review we discuss mechanisms that react t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 146 publications
(144 reference statements)
1
40
0
2
Order By: Relevance
“…Metrics related to reproductive history are not commonly included in breast cancer clinical data sets, such that the number of breast cancers that meet the definition of PPBC is currently derived from best estimates. One approach to estimate global burden of PPBC is to utilize data obtained from developed countries, which show that ~13% of all breast cancers are YWBC (27,28) and that ~50% of these cases have likely completed a pregnancy within 10 years of their diagnosis (29). This approach results in a global estimation of ~130,000 PPBC cases per year.…”
Section: Text Box #1mentioning
confidence: 99%
See 1 more Smart Citation
“…Metrics related to reproductive history are not commonly included in breast cancer clinical data sets, such that the number of breast cancers that meet the definition of PPBC is currently derived from best estimates. One approach to estimate global burden of PPBC is to utilize data obtained from developed countries, which show that ~13% of all breast cancers are YWBC (27,28) and that ~50% of these cases have likely completed a pregnancy within 10 years of their diagnosis (29). This approach results in a global estimation of ~130,000 PPBC cases per year.…”
Section: Text Box #1mentioning
confidence: 99%
“…Pregnancy both promotes and protects against breast cancer (29)(30)(31). All parous women are under a 10-30% increased risk of developing breast cancer for at least a decade after childbirth in comparison to nulliparous young women, with older age at first birth increasing the magnitude of risk (31).…”
mentioning
confidence: 99%
“…In addition, epidemiological studies have found that reproductive history is linked to the development of breast cancer. The risk of breast cancer is significantly less in early pregnancy (before age 20), while the risk transiently increases after parturition [91,93]. Peri et al [94] have demonstrated that hnRPA2B1 is overexpressed in the mammary tissues of post-menopausal parous women, suggesting that m 6 A modification may contribute to the correlation between pregnancy and breast cancer.…”
Section: Roles Of M 6 a In The Clinicopathology And Prognosis Of Breamentioning
confidence: 99%
“…In humans an apparent lifelong natural protection is obtained by full term pregnancy somewhat depending on the age at which pregnancy begins 1 . The greatest protection is obtained when the first full term birth occurs before the age of twenty, and parity continues to impact positively until the early thirties (reviewed in 2 , 3 ). The protective effect only pertains to estrogen receptor-positive (ER pos ) breast cancer, which is particularly interesting because of its relatively late onset in postmenopausal women 2 .…”
Section: Introductionmentioning
confidence: 99%
“…That estrogens play a role in breast cancer prevention is suggested from studies in rodents where artificial imitation of the hormonal milieu of pregnancy confers the same protection as does pregnancy 4 . While the exact molecular mechanisms affording such protection are still far from understood (reviewed in 3 ), it has been speculated that protection relates to either long-lasting cell autonomous alterations in the breast stem cell hierarchy or persistent changes in the systemic or microenvironmental hormonal milieu—or both 2 . Nevertheless, whether ER pos cells participate in conveying this protection has remained an enigmatic question for decades.…”
Section: Introductionmentioning
confidence: 99%